MULTIDRUG RESISTANT MYCOBACTERIUM TUBERCULOSIS IN ADAMAWA STATE, NIGERIA - Omisore, Nusirat Omotayo; Oyewole, Mukaila Oyeleke; Akinkunmi, Ezekiel Olugbenga (African Journal of Infectious Diseases (AJID), 2018)
Background: There is a need to have regular updates from regions where high burden of tuberculosis (TB) have been reported in order to assist the local and global bodies in their objective to curtail the spread of drug resistant TB (DRTB). This study presents a situation report of DRTB in Adamawa State which has been identified as one of the States with high burden of TB in Nigeria. Materials and Methods: Sputum culture in Lowenstein-Jensen Media, drug sensitivity tests and the GeneXpert MTB/Rif analysis were used in the identification and drug susceptibility studies of M. tuberculosis isolates obtained from forty TB patients who were enrolled from three selected hospitals with DOTS facilities in the State. Results: The age of TB patients range from 17 to 70 years (median = 30 years). Twenty (50 %) M. tuberculosis isolates were detected by the GeneXpertMTB/Rif analysis while the media culture detected 31 (77.5%). The two methods however detected rifampicin resistance in 4 (10%) of the total isolates. All rifampicin resistant isolates were multidrug resistant TB (MDRTB) and three of them were from male patients aged 30, 38 and 45. There was only one case of resistance to streptomycin, 3 to ethambutol and 6 to isoniazid. Monoresistance were only observed for ethambutol and isoniazid and it was found in two isolates for each. Conclusion: There is a need to provide interventions to control MDRTB in the state and to make such interventions available and closer to the patients.